CHECKLIST OF TUNNELLING DUNG BEETLES (COLEOPTERA: SCARABAEIDAE) IN LAI CHAU PROVINCE WITH THE FIRST REPORT OF NEW PROVINCIAL RECORDS - Van Bac, Bui (Journal of Forestry Science and Technology, 2020)
Dung beetles (Coleoptera, Scarabaeidae) are recognised as good indicators in many tropical forests, but little is known about their community composition in tropical karst ecosystems. This study investigated the species composition of tunnelling dung-beetles inhabiting arable land of karst ecosystems in Lai Chau province. Tunnellers were by far the dominant functional group of dung beetles in these ecosystems. The dung-beetle sampling was conducted in the rice, corn and tea fields of karst ecosystems in Sin Ho district and Lai Chau city. A total of 45 baited pitfall traps were deployed to collect tunnelling dung-beetles between August and November 2019. Nine tunnelling dung-beetles were recorded during the dedicated surveys of this study, increasing the number of tunnelling dung-beetles known to date to 16 species in Lai Chau province. Of which, two species, Synapsis tridens Sharp, 1881 and Liatongus gagatinus (Hope, 1831) were recorded for the first time in Lai Chau. In the following, I re-described these two species, including detailed illustrations and morphometrics of both sexes. At the same time, updated data on the distribution and habitat notes of the two tunnelling dung-beetles were given. The first checklist of tunnelling dung beetles (Coleoptera: Scarabaeidae) in Lai Chau province was also complied.